(untitled) (International Journal of Food and Nutritional Sciences, 2024)
CSR (CSR) has evolved from a philanthropic activity into a strategic institutional function influencing employee involvement, organizational reputation, competitive advantage, and long-term financial sustainable development. In the contemporary digital economy, Information Technology (IT) organizations increasingly integrate CSR and Environmental, Social, and Governance (ESG) principles into corporate strategy to enhance stakeholder trust and sustainable performance. This research paper critically examines the conceptual relationship between CSR strategic inclusion and institutional outcomes within selected IT organizations in Pune—Infosys, Tata Consultancy Services (TCS), Tech Mahindra, and HCL Technologies. The research is based upon the conceptual framework: CSR strategic inclusion → employee involvement → organizational reputation → long-term business performance The paper employs a systematic literature review methodology and critically synthesizes academic literature, ESG disclosures, sustainable development reports, annual reports, and institutional studies related to CSR, employee involvement, reputation management, and long-term business performance. The findings suggest that strategic CSR strategic inclusion positively influences employee commitment, institutional identity, stakeholder trust, employer branding, and organizational reputation, which subsequently contribute toward long-term financial sustainable development and competitive advantage. However, the research also identifies challenges related to ESG transparency, employee well-being concerns, greenwashing, and limitations in measuring CSR outcomes. The paper contributes toward understanding CSR as a multidimensional strategic framework within India’s IT industry and proposes an integrated conceptual model linking sustainable development governance with institutional performance.